Surgical management of giant pituitary adenomas: institutional experience and clinical outcomes of 94 patients - Ke, Daibo; Xu, Ling; Wu, Danyang; Yang, Shaocheng; Liu, Shun; Xie, Mingxiang; Xiao, Shunwu (Frontiers in Oncology, 2023)
Background Giant (with a diameter of at least 40 mm and a volume of at least 10 cm3) pituitary adenomas (GPAs) are intricate tumors that pose considerable difficulty for surgical removal. While endoscopic transsphenoidal surgery (ETS) is a commonly employed technique for these destructive tumors, its effectiveness may be restricted in cases where invasion into multiple compartments is present, leading to limited resection. Methods A retrospective review was conducted on the clinical records of 94 patients diagnosed with GPAs who had undergone surgical resection from 2014 to 2022. An analysis was conducted on the outcomes of the surgical and clinical procedures. Results In this group, the average size of the tumor before surgery was 44.6 ± 5.6 mm (range, 40–73 mm), and the volume was 25. 5± 16.6 cm3 (range, 10–20.67 cm3). Of the total number of patients, 72 (76.6%) underwent a single ETS, 12 (12.8%) opted for transcranial surgery (TCS), and 10 (10.6%) chose a combined method. Gross total resection (GTR) was successfully performed in 49 (68.1%), 3 (25.0%), and 8 (80.0%) patients who underwent each surgical approach. Seventy-four (78.7%) patients had improved vision, 20 (21.3%) were unchanged, and none had deterioration. Twenty-two patients (23.4%) experienced a total of 43 complications, which comprised hormonal insufficiency (11/94, 11.7%), diabetic insipidus (6/88, 6.8%), electrolyte disorders (7/94, 7.4%), cerebrospinal fluid leakage (5/94, 5.3%), meningitis (8/94, 8.5%), and hydrocephalus (6/94, 6.4%). The GTR, subtotal resection (STR), and partial resection (PTR) rates were 63.8% (60/94), 21.3% (20/94), and 14.9% (14/94), respectively. Throughout the follow-up duration, 18.1% (17/94) of patients required reoperation and/or adjuvant radiation treatment as a result of tumor regrowth or inadequate biochemical remission of functioning GPAs. Conclusion ETS remains the optimal surgical option for most GPAs and generally offers safe and efficient tumor resection. However, a combined approach with TCS remains a requirement in cases that are not suitable for treatment with a single ETS. To achieve optimal tumor removal and minimize the occurrence of surgical complications, a flexible combination of ETS and TCS is recommended based on the characteristics of the tumor.